Karakteristik Soliton Pada Persamaan Schrödinger Nonlinear - Prayitno, T. B. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2013)
It has been calculated in this manuscript the characteristic possessed by soliton of nonlinear Schrödinger equation in the case of (1+1) space-time dimension. In thus case, it will be discussed two physical entities, namely, classical mass and topological charge of nonlinear Schrödinger equation. Especially for the classical mass, we comment about the resulting calculation in the previous paper [Berkala Fisika Vol. 14, 75 (2011)] since there is such a wrong calculation that it can cause wrong interpretation. This interpretation is related to the relativistic property owned by the soliton as the manifestation of the particle nature. Besides we also prove that the value of topological charge in the nonlinear Schrödinger is zero. Keywords: Soliton, Schrödinger nonlinear, muatan topologi.